Prevalence of Skin morbidity among construction site workers working at Vadodara - Trivedi Ashish; Patel Yogesh; Pandit Niraj; Bhavsar Bharat (Indian Association of Preventive and Social Medicine, 2011)
Abstract Background: Construction workers are the second largest workforce in un-organized sector of the country. They are exposed to various hazards due to work conditions. Occupational Dermatitis is one of the commonest hazards among construction workers, most commonly due to exposure to cement and other materials like paints and resins, used at construction sites. Objectives: To find out prevalence of skin morbidity and its relation with provision and practice of usage of Personal Protective Equipments (PPEs) among construction workers. Methodology: A cross sectional study among construction workers working at various sites of Sumandeep Vidyapeeth. Data was collected with the help of a pre-designed and pre-tested questionnaire for skin morbidity. Results: 20.3% of workers had skin morbidity like dermatitis and itching. Only 28(12.5%) out of 230 workers were provided the PPEs at workplace, however, only eight were using them regularly during work and it was found that prevalence of skin morbidity was less in this group compared to the group which was not using them regularly at workplace. Conclusion: Skin morbidity is one of the commonest hazards among construction workers. Morbidity is lesser among regular PPE users at workplace.